Suffrage : women's long battle for the vote - DuBois, Ellen Carol, 1947- (Simon & Schuster, 2020)
Distinguished historian Ellen Carol DuBois begins in the pre-Civil War years with foremothers Lucretia Mott, Elizabeth Cady Stanton, Susan B. Anthony, and Sojourner Truth as she explores the links of the woman suffrage movement to the abolition of slavery. After the Civil War, Congress granted freed African American men the right to vote but not white and African American women, a crushing disappointment. DuBois shows how suffrage leaders persevered through the Jim Crow years into the reform era of Progressivism. She introduces new champions Carrie Chapman Catt and Alice Paul, who brought the fight into the 20th century, and she shows how African American women, led by Ida B. Wells-Barnett, demanded voting rights even as white suffragists ignored them. DuBois explains how suffragists built a determined coalition of moderate lobbyists and radical demonstrators in forging a strategy of winning voting rights in crucial states to set the stage for securing suffrage for all American women in the Constitution. In vivid prose DuBois describes suffragists<U+2019> final victories in Congress and state legislatures, culminating in the last, most difficult ratification, in Tennessee. DuBois follows women<U+2019>s efforts to use their voting rights to win political office, increase their voting strength, and pass laws banning child labor, ensuring maternal health, and securing greater equality for women.